2020
DOI: 10.1111/tmi.13367
|View full text |Cite
|
Sign up to set email alerts
|

Quantity vs. quality: an assessment of the current pipeline for rabies

Abstract: objectives To gain insight in the potential of the current pipeline for rabies to decrease the burden of disease by evaluating its relevance to high-risk countries.methods Rabies-related patent documents and clinical trials were retrieved from Espacenet and the WHO ICTRP, respectively. Data were cleaned, modulated and categorised into a pre-defined set of indicators those were used for (statistical) analyses on the number of patent applications, patent quality and type of stakeholders involved for different ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Most inventions in the pharmaceutical sector are covered by patents as they are the only way of offering solid intellectual property protection of new pharmaceutical compounds. 15 Clinical trials represent late-stage drug development that all new inventions must pass before market entry, which make clinical trials a reliable indicator of the short-term market entry. However, a significant share of inventions disclosed in patents will not enter clinical testing due to disappointing research results, or due to strategic reasons.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most inventions in the pharmaceutical sector are covered by patents as they are the only way of offering solid intellectual property protection of new pharmaceutical compounds. 15 Clinical trials represent late-stage drug development that all new inventions must pass before market entry, which make clinical trials a reliable indicator of the short-term market entry. However, a significant share of inventions disclosed in patents will not enter clinical testing due to disappointing research results, or due to strategic reasons.…”
Section: Methodsmentioning
confidence: 99%
“…The final list of 189 patents was further analyzed to visualize time and geographical trends. In line with criteria for asssessing quantity over quality 15 , we also looked into high quality patents, here defined as being cited more times.…”
Section: Data Collection and Selectionmentioning
confidence: 99%
“…To identify relevant clinical studies, the EU clinical trials register (CTR.eu), the United States NLM database (CT.gov), and the International Clinical Trials Registry Platform (ICTRP) were queried, as these are regularly updated and contain records of clinical trials from 202 countries, covering a total of 17 different clinical trial databases ( World Health Organization, 2021 ). The selection of these databases is in line with previous research in this field ( Ramezanpour et al, 2015 ; Janse et al, 2020 ; Neevel et al, 2020 ).…”
Section: Methodsmentioning
confidence: 92%
“…Analogous to these sales estimates, it was found that Asia and North America were the most popular locations for clinical trials and patent applications. According to Neevel et al (2020) , the location of patent applications is closely related to expected profit, as the costs of patent filing and maintenance are very high. Lower-income countries were less frequently reported as the patent application and clinical trial locations.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high costs related to patenting, there is a direct relation between the location of patent applications and target markets. Patents are generally only applied for in countries where they are expected to bring a substantial economic benefit, either by generating revenues or by preventing competitors to enter the market [ 33 ]. Patent families for which only documents with kind codes belonging to the World Intellectual Property Organisation (WIPO) or European Patent Office (EPO) were categorized as a separate group.…”
Section: Methodsmentioning
confidence: 99%